Exploring glycosyl sulphates as donors for chemical glycosylation. Issue 22 (13th May 2021) - Imperio, Daniela; Campo, Federica; Panza, Luigi
Abstract : Anomeric sulphates give efficient glycosylation reactions with both acidic and basic promoters. Abstract : The preparation of anomeric tetrabutylammonium sulphates of glucose and galactose derivatives is reported and their role as donors in glycosylation reactions is studied. Metal triflates showed good performance in activating sulphate as a leaving group. Among them, ytterbium triflate in stoichiometric amounts gave the best results. Basic conditions using barium oxide in combination with trimethylsilyl trifluoromethanesulfonate (TMSOTf) were also shown to give good results. Benzylated sulphates were much more reactive than benzoylated donors when activated either by ytterbium triflate or by BaO and TMSOTf. Different acceptors were tested, such as isopropanol, cholesterol, and other common sugar derivatives. High reaction rates and excellent glycosylation yields were obtained under mild reaction conditions. The α/β anomeric ratio suggests a predominant SN 2-like reaction mechanism.